Onomatopoeia Analysis on Doctor Dolittle Novel by Hugh Lofting - Diani Syahputri; Ratna Sari Dewi; Ambar Wulan Sari; Tengku Winona Emelia (English Teaching and Linguistics Journal (ETLiJ), 2023)
This study deals with onomatopoeia in Doctor Dolittle novel by Hugh Lofting. The objectives of the study were to analyze the types of onomatopoeia that used in the Doctor Dolittle novel by Hugh Lofting, to analyze why onomatopoeia used in Doctor Dolittle novel by Hugh Lofting, and to investigate how the author describe the onomatopoeia word in his novel. The scope and limitation were focused about onomatopoeia words found in the Doctor Dolittle novel by Hugh Lofting. The researchers analyzed three types of onomatopoeia, there are Direct Onomatopoeia, Associative Onomatopoeia, and Exemplary Onomatopoeia. This study applied a descriptive qualitative method. The source of data  was taken from the Doctor Dolittle novel. The technique of data analyzing used data presentation, data verification and, data reduction. The research finding showed that there were 38 of onomatopoeia found in this research which consist of 7 words direct onomatopoeia,24 words assiciative onomatopoeia, and 7 exemplary onomatopoeia based on Bredin's (1996 : 558). Associative Onomatopoeia was the dominant types of Doctor Dolittle novel by Hugh Lofting.